2010
DOI: 10.1111/j.1369-7625.2010.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

The integration of citizens into a science/policy network in genetics: governance arrangements and asymmetry in expertise

Abstract: Objectives While there are increasing calls for public input into health research and policy, the actual obtaining of such input faces many challenges in practice. This article examines how a Canadian science ⁄ policy network in the field of genetics integrated citizens into its structure and then managed their participation.Methods Our ethnographic case study covers a 5-year period and combines four data sources: observations of the networkÕs meetings and informal activities, debriefing sessions with the net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…In such cases, members of the pub lic can become disengaged if they feel their participation is not relevant or tokenistic [25]. It is important to be upfront with participants of public engagement exercises about what they are expected to contribute and how it might be used by policy and decisionmakers (if at all).…”
Section: Conclusion: Lessons Learned From Public Engagement With Persmentioning
confidence: 97%
See 4 more Smart Citations
“…In such cases, members of the pub lic can become disengaged if they feel their participation is not relevant or tokenistic [25]. It is important to be upfront with participants of public engagement exercises about what they are expected to contribute and how it might be used by policy and decisionmakers (if at all).…”
Section: Conclusion: Lessons Learned From Public Engagement With Persmentioning
confidence: 97%
“…Case studies such as these are especially informative; they reveal not only the pragmatic and policy out comes of engagement efforts (e.g., influencing the choice of biobank consent processes), but also the challenges of community engagement (e.g., engaging with the public on a topic about which many claim they are uninformed or find ing a diverse range of stakeholders for advisory groups and panels). Similarly, an ethnographic case study of a Canadian science/policy network in the field of genetics revealed how difficult obtaining and sustaining public input could be in this context [25]. Citizen representatives were invited to join the network 2 years after it was established, with neither the dynamics nor www.futuremedicine.com and knowledge production to be more 'democratic'; to contribute to a better understanding of citizen involvement in transdisciplinary networks Partial citizen involvement in the network; lessons learned by highlighting the challenges arising from citizen inclusion in a pre-established science/policy network [25] Etchegary et al…”
Section: Public Engagement Initiatives With Personalized Medicinementioning
confidence: 97%
See 3 more Smart Citations